Exploring the Views of Healthcare Professionals Working in a Mental Health Trust on Pharmacists as Future Approved Clinicians - Balazs Adam; Richard N. Keers (MDPI AG, 2022)
This qualitative research explored the views and attitudes of healthcare professionals towards the role of the mental health pharmacist, and whether this group should be enabled to become approved clinicians (ACs) in England and Wales under the Mental Health Act in future. Following ethical approval, recruitment based on systematic purposive sampling principles took place at one mental health trust in England. Six pharmacists, five medical ACs and two mental health nurses participated in one-to-one digitally audio-recorded semi-structured interviews between June and November 2020. The recordings were transcribed verbatim before being inductively coded and thematically analysed. Notwithstanding the wide recognition among participants of several key skills possessed by mental health pharmacists, various obstacles were identified to them becoming ACs in future, including prevalent conventional models of pharmacy services delivery restricting adequate patient access, as well as insufficient training opportunities to acquire advanced clinical skills, particularly in diagnosis and assessment. In addition to the inherent legislative hurdles, fundamental changes to the skill mix within multidisciplinary mental health teams and improvements to the training of pharmacists were reported by participants to be required to equip them with essential skills to facilitate their transition towards the AC role in future. Further research is needed to gain a better understanding of the challenges facing the clinical development and enhanced utilisation of mental health pharmacists and non-medical ACs across services.